El lustro dorado de los intercambios entre intelectuales estadounidenses y ecuatorianos: 1940-1945 (Crítica) - Moret, Marlene (2025)
In the context of Franklin D. Roosevelt’s Good Neighbor Policy and the rapprochement promoted by several American institutions at the beginning of World War II, the 1940s were a time of intense exchanges between American and Ecuadorian intellectuals, a fruitful parenthesis after the anti-imperialist stances of the previous decades and before the ideological and political confrontations of the Cold War. The author studies this special moment through the exchanges between four American intellectuals, Albert B. Franklin, Thornton Wilder, Willis Knapp Jones and John Dos Passos, and three members of the Grupo de Guayaquil: Demetrio Aguilera Malta, Alfredo Pareja Diezcanseco and Enrique Gil Gilbert, based on unpublished letters and documents, and with an emphasis on the literary contest of the Pan-American Union (1941).